The Training Effort for Master Athletes in Romania in Relation to Self-esteem - Balint Lorand; Baba Daniela (Revista Românească pentru Educaţie Multidimensională, 2022)
The aim of this article is to study the relationships between the training effort of master athletes (+35 years), performed by endurance running in order to participate in running events and their self-esteem. The research method was the investigation. The tool used was a questionnaire especially created for this research that also contains the Rosenberg Self-Esteem Scale. Out of the 111 participants, 62.2% are men and 37.8% are women. Men make a great effort (>12 km/training) 2,229 days/week, compared to women, who make a great effort 1.46 days/week, resulting in a significant difference (t = 2.53, p <0.05). The results revealed a statistically significant correlation between the self- attitude changes by running and health changes (r=0.46, p =0.01) and between the self-esteem attitude changes by practicing running and the small intensity weekly effort (< 8km/workout), (r =0.218, p=0.05). Conclusions: we believe that in terms of encouraging people of all ages to practice outdoor sports, promoting a healthy lifestyle based on exercise and managing mass sports, paying attention to endurance running is of extreme importance, especially in this stressing times that we are living. Therefore, a small to medium weekly effort is a self-disciplined habit that maintains the optimal health of the body and contributes to good self- esteem. The benefit resulting from the training effort gives the individual a state of well-being (67% of the participants had as their main motivation to run, a good state) which contributes to an increased in self-esteem. We consider that a high level of self-esteem is good not only for the individual, but also for the entire society. There are studies concerning the self-esteem in the literature of speciality, but not about the relation between amateur athletes’ training and self-esteem. We consider that the master athletes could be a rich source of information when studying the self-esteem.
Keywords: athlete masters; training; self-esteem; running